Coffee, Community, and Capitalism: Analyzing Worker Economic Strategies at Blawan Plantation in East Java (2016-2022) - Winarni, Retno; Widuatie, Mrr. Ratna Endang; Sasmita, Nurhadi; Endrayadi, Eko Crys (Yupa: Historical Studies Journal, 2025)
This article is written to discuss and describe the influence of the Blawan coffee plantation on the economic resilience of the workers' families in Kalianyar Village, Ijen Subdistrict, Bondowoso Regency (2016-2022) with an economic sociology approach. The theoretical framework used in this article is the theory of social change. Methodologically, the article uses the historical method, which includes heuristics, criticism, interpretation, and historiography. From the results of the research, it is known that the Blawan coffee plantation became the foundation of hope for workers in Kalianyar village to meet the economic needs of the family and the workers can be involved in activities in the plantation starting from the production process, plant maintenance, coffee harvesting process, and post-harvest coffee handling. From these major activities, the laborers get income to help the family economy. The conclusion is that the Blawan coffee plantation is the foundation of the laborers' hopes to improve the family economy.